The Multicultural Education in Indonesia: The Perspective of Islamic Educational Philosophy - Binti Muawanah; Ari Purnomo; Ari Hesti Fauzi; Annisa Noer Maydifika; Fitri Nur Hidayati; Imam Sayuti; Lisnawati; Muhammad Amir; Nirmala Ade (Bulletin of Pedagogical Research, 2021)
Multicultural education in Indonesia plays a strategic role in managing the nation's rich diversity of cultures, ethnicities, religions, and languages. From the perspective of Islamic educational philosophy, it offers a normative and ethical foundation to foster harmony amid differences. This study views multicultural education as a conscious effort to cultivate awareness and tolerance by appreciating the values of pluralism in alignment with core Islamic principles such as justice, equality, and respect for human rights. Islamic educational philosophy emphasizes the importance of tauhid (the oneness of God) as the foundation for shaping inclusive character that respects diversity. Through this approach, multicultural education aims not only to develop students’ intellectual competence but also to nurture their moral and ethical capacity to live peacefully in a pluralistic society. This study recommends integrating multicultural and Islamic values into the educational curriculum to cultivate a generation that is tolerant, socially just, and capable of embracing diversity as a national asset.Keyword : Pendidikan, Multikulrural, Filsafat